Integrasi Nilai-Nilai Islam dalam Edukasi Energi Hijau: Pengembangan Website Islamic Green Energy di Perguruan Tinggi - Muhammad, Muhammad; Sulastri, Sulastri; Hidayat, Taufik; Al Farouqh, Rhizieq Reflian; Fatkhurrohmat, Muhammad Brillian Maulana (Medan Resource Center, 2026)
Environmental and energy issues have become global concerns due to the increasing impacts of climate change. Education plays a strategic role in fostering awareness and responsibility among younger generations regarding sustainable energy management. In the Indonesian context, where the majority of the population is Muslim, integrating Islamic values into green energy education is highly relevant to strengthen ecological awareness and ethical responsibility toward the environment. However, studies that systematically integrate Islamic values into digital platforms for green energy education remain limited. This study aims to develop an educational digital media in the form of a website that integrates green energy learning with Islamic values for use in higher education. The research employed a Research and Development (R&D) approach based on the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation. Data were collected through a needs assessment survey, expert validation, and user feasibility testing involving respondents, and were analyzed using descriptive statistical techniques. The results indicate that the developed website, “Islamic Green Energy,” achieved a very high feasibility level based on expert validation with a score of 90.38%, and received highly positive responses from users, with all evaluation indicators scoring above 85%. These findings suggest that the website is considered appropriate and user-friendly as a digital learning medium for introducing green energy concepts integrated with Islamic values. The novelty of this research lies in the systematic integration of Islamic ethical values into a digital green energy education platform, contributing to the development of value-based digital learning media in sustainable energy education at the higher education level.